IMMUNOCHEMICAL ANALYSIS OF THE EXPRESSION OF SV2C IN MOUSE, MACAQUE AND HUMAN BRAIN - Dunn, Amy R. (Brain Res, 2017)
The synaptic vesicle glycoprotein 2C (SV2C) is an undercharacterized protein with enriched expression in phylogenetically old brain regions. Its precise role within the brain is unclear, though various lines of evidence suggest that SV2C is involved in the function of synaptic vesicles through the regulation of vesicular trafficking, calcium-induced exocytosis, or synaptotagmin function. SV2C has been linked to multiple neurological disorders, including Parkinson’s disease and psychiatric conditions. SV2C is expressed in various cell types—primarily dopaminergic, GABAergic, and cholinergic cells. In mice, it is most highly expressed in nuclei within the basal ganglia, though it is unknown if this pattern of expression is consistent across species. Here, we use a custom SV2C-specific antiserum to describe localization within the brain of mouse, nonhuman primate, and human, including cell-type localization. We found that the immunoreactivity with this antiserum is consistent with previously-published antibodies, and confirmed localization of SV2C in the basal ganglia of rodent, rhesus macaque, and human. We observed strongest expression of SV2C in the substantia nigra, ventral tegmental area, dorsal striatum, pallidum, and nucleus accumbens of each species. Further, we demonstrate colocalization between SV2C and markers of dopaminergic, GABAergic, and cholinergic neurons within these brain regions. SV2C has been increasingly linked to dopamine and basal ganglia function. These antisera will be an important resource moving forward in our understanding of the role of SV2C in vesicle dynamics and neurological disease.